Chromium improvements on the mechanical performance of a rapidly solidified eutectic Sn-Ag alloy - Gumaan, Mohammed S. (Springer Nature, 2020)
The eutectic Sn-Ag alloy considered a good replacement to the conventional solders. This study aims to enhance the mechanical performance of the eutectic Sn-Ag alloy in terms of both elasticity and plasticity through investigating the effects of chromium (Cr) content with x?=?1, 3, and 5 wt.% on the mechanical and thermal properties of melt-spun Sn-3.5%Ag alloy. Ternary melt-spun Sn-Ag-Cr alloys investigated using x-ray diffractions (XRD), Scanning electron microscope (SEM), Instron machine, Vickers hardness tester, and Differential scanning calorimetry (DSC). The results revealed that the Cr content modifies the microstructure by refining the microstructure of the matrix of Sn solder; suppressing coarse intermetallic compound (IMC) formation; and changing the morphology of the IMC in Sn solder. The high concentration of multi-oriental Ag3Sn that formed with 3 wt.% of Cr, in addition to the compatibility among ?-Sn (Tetragonal), Ag3Sn (004) (orthorhombic), and Cr (200) (bcc), enhance the elasticity of melt-spun Sn93.5-Ag3.5-Cr3 solder alloy by 330% (87.98 GPa) and obstructed the fracture process. The tensile test for that melt-spun alloy (3 wt.% of Cr) showed obvious improvements in ultimate tensile strength (UST) by 19% (23.42 MPa), and in toughness by 15.31% (911.15 J m?3) compared to that of the eutectic melt-spun Sn-Ag alloy. Its hardness (Vickers hardness) value has improved by 22.37% (171.50 GPa) compared with that of the eutectic melt-spun Sn-Ag alloy. Slight improvements in thermal performance for that alloy have appeared through thermal conductivity by 8% (49.971 w m?1 k?1) and thermal diffusivity by 85.4% (2.758??10-7 m2 s-1) compared to that of the eutectic melt-spun Sn-Ag alloy. All of the above-mentioned improvements are related to the microstructural changes with 3 wt.% of Cr to the eutectic Sn-Ag alloy. The high elasticity, high plasticity, low ?T, and relatively low melting temperature (Tm) that have been taking place with 3 wt.% of Cr are suggested to increase the mechanical reliability of this alloy to become more desirable in soldering applications and electronic assembly.